The Effect of Academic Supervision and Work Motivation on Teacher Performance at Pembina State Kindergarten - Retno Rakhmi F; Jumintono Jumintono; Rahmat Mulyono (EDUJAVARE: International Journal of Educational Research, 2026)
This study aimed to improve the quality of instructional implementation through academic supervision at TK Pertiwi Dinas P dan K Wonosobo academic year. The research employed a School Action Research design consisting of two cycles, with each cycle involving planning, implementation, observation, and reflection stages. The subjects of the study were two kindergarten teachers. Data were collected through classroom observations, supervision instruments, and reflective discussions. The findings revealed that academic supervision significantly improved teacher performance in implementing learning activities. In the pre-cycle stage, teachers’ performance was still categorized as moderate and adequate, with scores of 65 and 75. Following the implementation of academic supervision in Cycle I, teacher performance improved, with scores increasing to 75 and 80. Further improvement was observed in Cycle II, where both teachers achieved good performance categories with scores of 85 and 87. The improvement was attributed to systematic supervision activities, including classroom observation, professional guidance, constructive feedback, motivation, and reflective evaluation. The study also found that increased teacher motivation contributed positively to instructional effectiveness, confidence, and commitment to implementing lesson plans. These findings indicate that academic supervision is an effective strategy for enhancing teacher professionalism and improving the quality of learning implementation in early childhood education institutions. Therefore, school principals are encouraged to conduct continuous academic supervision as part of sustainable teacher professional development programs to achieve better educational outcomes.